Auroral, Ionospheric and Ground Magnetic Signatures of Magnetopause Surface Modes. Issue 3 (3rd March 2023) - Archer, M. O.; Hartinger, M. D.; Rastätter, L.; Southwood, D. J.; Heyns, M.; Eggington, J. W. B.; Wright, A. N.; Plaschke, F.; Shi, X.
Abstract: Surface waves on Earth's magnetopause have a controlling effect upon global magnetospheric dynamics. Since spacecraft provide sparse in situ observation points, remote sensing these modes using ground‐based instruments in the polar regions is desirable. However, many open conceptual questions on the expected signatures remain. Therefore, we provide predictions of key qualitative features expected in auroral, ionospheric, and ground magnetic observations through both magnetohydrodynamic theory and a global coupled magnetosphere‐ionosphere simulation of a magnetopause surface eigenmode. These show monochromatic oscillatory field‐aligned currents (FACs), due to both the surface mode and its non‐resonant Alfvén coupling, are present throughout the magnetosphere. The currents peak in amplitude at the equatorward edge of the magnetopause boundary layer, not the open‐closed boundary as previously thought. They also exhibit slow poleward phase motion rather than being purely evanescent. We suggest the upward FAC perturbations may result in periodic auroral brightenings. In the ionosphere, convection vortices circulate the poleward moving FAC structures. Finally, surface mode signals are predicted in the ground magnetic field, with ionospheric Hall currents rotating perturbations by approximately (but not exactly) 90° compared to the magnetosphere. Thus typical dayside magnetopause surface modes should be strongest in the East‐West ground magnetic field component. Overall, all ground‐based signatures of the magnetopause surface mode are predicted to have the same frequency across L ‐shells, amplitudes that maximize near the magnetopause's equatorward edge, and larger latitudinal scales than for field line resonance. Implications in terms of ionospheric Joule heating and geomagnetically induced currents are discussed. Plain Language Summary: Waves on the boundary of the magnetosphere, the magnetic shield established by the interplay of the solar wind with Earth's magnetic field, play a controlling role on energy flow into our space environment. While these waves can be observed as they pass over satellites in orbit, due to the small number of suitable satellites available it would be helpful to be able to detect these waves from the surface of the Earth with instruments that measure the northern/southern lights, motion of the top of our atmosphere, or magnetic field on the ground. However, we do not currently understand what the signs of these waves should look like in such instruments. In this paper we develop theory and use computer simulations of these boundary waves to predict key features one might expect to measure from the ground. Based on these predictions, we also discuss how the waves might contribute to the hazards of space weather. Key Points: Theory and global simulations of magnetopause surface waves' effects on the aurorae, ionosphere, and ground magnetic field are investigated We predict poleward‐moving periodic aurora, convection vortices, and ground pulsations, with larger latitudinal scales than Alfvén modes Amplitudes of all signals peak near the projection of the inner/equatorward edge of the magnetopause rather than the open–closed boundary